Seed Sources for Florida Homegrown Vegetables - Ed Thralls; Sydney Park Brown; Ed Paulson (EDIS, 2013)
The right vegetable varieties can make a big difference in the success of a home vegetable garden. Although a huge selection of seeds and transplants are available through garden centers, seed catalogs, and the internet, choosing what to buy can be confusing. Some of the best varieties for Florida gardens and seed suppliers that currently sell them are listed in this 6-page fact sheet written by Ed Thralls, Sydney Park Brown, and Ed Paulson, and published by the UF Department of Environmental Horticulture, November 2013. http://edis.ifas.ufl.edu/ep486